A study on the nursing knowledge, attitude, and performance towards pressure ulcer prevention among nurses in Korea long‐term care facilities - Kim, Jung Y. (Int Wound J, 2019)
This study aimed to investigate Korean nurses' level of knowledge, attitude, and performance of pressure ulcer prevention in long‐term care facilities. A descriptive study was performed. Convenience sampling was used, and registered nurses were recruited from the attendees of a continuing education programme for nurses in long‐term care facilities. A total of 282 participants (RN) completed the questionnaire. Data were collected from September to December 2015. Nurses participating in this study demonstrated a moderate level of knowledge of pressure ulcer prevention (60.1%) and exhibited positive attitudes towards pressure ulcer prevention (33.80 ± 2.48). Nurses regularly assessed the risk factors of pressure ulcers during the hospitalisation period for all patients in the hospital when performing pressure ulcer prevention care. However, the plan for preventive nursing care was not properly reviewed. It was also found that nurses did not consider changes in the patient's condition as important to why they had to change their nursing plans to prevent pressure ulcer. Therefore, this study suggested that appropriate guidelines, education programmes, and an environment that makes it possible to provide continuing education should be created for nurses to prevent pressure ulcers in Korea's long‐term care facilities.